Answer:
Step-by-step explanation:
Answer:
A.
Step-by-step explanation:
you have to find the discriminant
b²-4ac for each equation
if discriminant < 0 no real solutions because will be negative under the squareroot whhan you try to find the roots
if discriminant = 0 there is only one solution
if discriminant > 0 two real solutions
for your given problems
A. discriminant =(-2)²-4*2*15 will be negative
Answer:
39°
Step-by-step explanation:
A radius of a circle (segment CD) drawn to the point of tangency (D) intersects the tangent (line DE) at a 90-deg angle.
That makes m<D = 90.
m<D + m<C + m<E = 180
90 + 51 + m<E = 180
m<E = 39
2x + y = 7
substitute
2x + (x+1) =7
combine like terms
3x+1 =7
subtract 1 from each side
3x =6
divide by 3
x=2
y = x+1
y =2+1
y=3
Answer: x=2, y=3
To solve this problem you must apply the proccedure shown below:
1. You have the following expression given in the problem above:
![( \frac{x^{2}-x-6}{4x^{3}}) (\frac{x^{2}+2x}{x^{2}+5x+6} )](https://tex.z-dn.net/?f=%20%28%20%5Cfrac%7Bx%5E%7B2%7D-x-6%7D%7B4x%5E%7B3%7D%7D%29%20%28%5Cfrac%7Bx%5E%7B2%7D%2B2x%7D%7Bx%5E%7B2%7D%2B5x%2B6%7D%20%29%20)
2. First, you must factor the polynomials in the numerator and in the denominator and then simplify the expression:
![(\frac{(x-3)(x+2)}{4x^{3}} ) (\frac{2x(x+1)}{(x+3)(x+2)})=\frac{(x-3)(x+1)}{2x^{2}(x+3)(x+2)}](https://tex.z-dn.net/?f=%20%28%5Cfrac%7B%28x-3%29%28x%2B2%29%7D%7B4x%5E%7B3%7D%7D%20%29%20%28%5Cfrac%7B2x%28x%2B1%29%7D%7B%28x%2B3%29%28x%2B2%29%7D%29%3D%5Cfrac%7B%28x-3%29%28x%2B1%29%7D%7B2x%5E%7B2%7D%28x%2B3%29%28x%2B2%29%7D%20%20%20)
The answer is: ![\frac{(x-3)(x+1)}{2x^{2}(x+3)(x+2)}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%28x-3%29%28x%2B1%29%7D%7B2x%5E%7B2%7D%28x%2B3%29%28x%2B2%29%7D%20%20%20)